Estudio de diferentes densidades de siembra en dos líneas promisorias de soya (Glycine max L. Merril ), en la zona de Babahoyo-Provincia de los Ríos - Aguilar Carrasco, Dennys Alexander (2014)
The investigation was conducted on june,6,2013, at the faculty of agricultural sciences, technical of Babahoyo wich is located at km 7 ½ way to Montalvo - Babahoyo of Los Rios provincia. The objective of this investigation is to determine the agronomie performance of cultivars of the two lines promising of soybeans of differents densities and establish performance based on the population and interaction locality of Babahoyo. The materials studied was lines of 10013 and 10485 planted population 80, 90, 100,110,120, kg/ha and the witness, the statical design was divided in two treatment plots (lines) six undertratment population and three repetitions. For the evaluation and comparasion the test was used tukey's test at 5% from probability.